Oil wealth in Central Africa : policies for inclusive growth - Akitoby, Bernardin; Coorey, Sharmini; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
Despite its vast oil wealth, central Africa still struggles to sustain strong, inclusive economic growth or to generate sufficient employment opportunities, particularly for its fast-growing youth population. Drawing on new research, this book lays out the macroeconomic and growth challenges facing the region; examines oil wealth management and its implications for poverty reduction; and includes four case studies that exemplify lessons learned.
Includes bibliographical references and index.
nif 17/05/13
Loan
Keywords: Petroleum industry and trade; Petroleum industry and trade - case studies; Natural resources; Natural resources - management - case studies; Economic development; Africa, Central